Perubahan Sosial Budaya Masyarakat Desa Ngebalrejo Akibat Kemajuan Ilmu Pengetahuan dan Teknologi - Maryanto Maryanto; Lilis Noor Azizah (Indonesian Journal of Social Science Education (IJSSE), 2019)
ABSTRACT:Socio-Cultural Changes in the Community of Ngembalrejo Village Due to the Advancement of Science and Technology. Socio-cultural change is a symptom of changing social and cultural conditions in a society. Socio-cultural changes are symptoms that always occur in every society. This study aims to: 1) describe the environmental conditions of the Ngembalrejo village. 2) describe the social activities of the community due to the advancement of science and technology. 3) describe the causes of socio-cultural changes in the context of the progress of science and technology. 4) describe the impact of socio-cultural changes for the people of Ngembalrejo village. Data was collected by interview techniques, as well as literature review, from books and journals related to socio-cultural changes due to the advancement of science and technology. The results of this study are: 1) local wisdom in the village of Ngembalrejo is a tradition of the community that contains values, and has been done for a long time from generation to generation, and has undergone changes. With the advancement of science and technology in the form of ideas and activities and about the relationship between humans and God, humans and humans, and their relationship with the environment. 2) the community views the importance of good social relations, in maintaining harmony. 3) there are causal factors and the impact of the changes in socio-cultural conditions of the village community which have resulted in differences in socio-cultural conditions in the previous year.ABSTRAK:Perubahan sosial budaya adalah gejala berubahnya kondisi sosial dan kebudayaan dalam suatu masyarakat. Perubahan sosial budaya merupakan gejala yang selalu terjadi pada setiap masyarakat.  Penelitian ini bertujuan untuk : 1) mendeskripsikan kondisi lingkungan desa Ngembalrejo. 2) mendeskripsikan aktivitas sosial masyarakat akibat kemajuan ilmu pengetahuan dan teknologi. 3) mendeskripsikan penyebab perubahan sosial budaya masyarakat dalam kontek kemajuan ilmu pengetahuan dan teknologi. 4) mendeskripsikan dampak perubahan sosial budaya bagi masyarakat desa Ngembalrejo. Data dikumpulkan dengan teknik wawancara, serta kajian kepustakaan, dari buku serta jurnal terkait perubahan sosial budaya akibat kemajuan ilmu pengetahuan dan teknologi. Hasil dari penelitian ini adalah : 1) kearifan lokal yang ada dalam desa ngembalrejo adalah tradisi masyarakat yang mengandung nilai-nilai, dan telah dilakukan sejak lama secara turun temurun, dan mengalami perubahan. Dengan adanya kemajuan ilmu pengetahuan dan teknologi dalam bentuk ide dan aktivitas serta tentang hubungan manusia dengan tuhan, manusia dengan manusia, serta hubungannya dengan lingkungan. 2) masyarakat memandang penting nya hubungan sosial yang baik, dalam menjaga keharmonisan. 3) terdapat faktor penyebab serta dampak dari adanya perubahan sosial budaya masyarakat desa yang mengakibatkan perbedaan kondisi sosial budaya pada tahun sebelumnya.